Baseline characteristics and follow-up outcomes in routine clinical practice patients categorised by renal function in the ETNA-AF-Europe registry. (25th November 2020) - De Caterina, R; Gwechenberger, M; Bakhai, A; Monteiro, P; Kelly, P; Levy, P; Kirchhof, P
Abstract: Background: Edoxaban is an oral factor Xa inhibitor anticoagulant with 50% renal clearance, and proven efficacy and safety in patients (pts) with atrial fibrillation (AF). The post-authorisation, observational, ETNA-AF-Europe registry (NCT02944019) assessed the risks and benefits of edoxaban in pts with AF from 10 European countries. Purpose: Evaluate baseline characteristics and event rates in pts categorised by creatinine clearance (CrCl) at 1-year follow-up of the ETNA-AF-Europe registry. Methods: In this analysis, pts were divided into three groups according to CrCl: ≤50 ml/min (I), 50–80 mL/min (II) and ≥80 mL/min (III) (calculated using Cockcroft-Gault). Outcomes were descriptively analysed. Results: Pts with the lowest CrCl (Group I) were mostly females, and had a higher mean age, lower body weight, higher stroke and bleeding risk scores and were considered more frail than those with higher CrCl (Groups II and III) (Table). Group I experienced higher rates of stroke or SEE, major or CRNM bleeding, cardiovascular death, and had a higher total mortality (Figure). Rates of intracranial haemorrhage (ICH) and haemorrhagic stroke (intracerebral and subarachnoid haemorrhage) were low and similar in pts across the range of CrCl. Conclusions: Those with lower CrCl had more comorbidities and higher event rates than those with higher CrCl, with the exception of ICH and haemorrhagic stroke. A steep rise in the proportion of pts perceived as frail and in overall mortality in the lowest renal function tertile, raises the question whether low renal function is a determinant or a correlate of mortality. Funding Acknowledgement: Type of funding source: Private company. Main funding source(s): Daiichi Sankyo Europe GmbH, Munich, Germany